Water stress effects on forage quality of alfalfa - A. Halim, Ridzwan; Buxton, D. R. (1988)
The objective of the experiment was to characterize effects of varying levels of water availability on plant composition as related to forage quality. Alfalfa (Medicago sativa L.) was grown in photometers and subjected to eight irrigation treatments. A well-irrigated control was compared with four treatments aimed at maintaining plants at various levels of water deficit through-out growth and with three treatments where water stress was applied at specific stages of growth. The intensity of water stress was expressed in terms of a crop-water-stress index, based on differences between air and canopy temperature. Plant maturity was delayed and internode length and plant height was depressed with increasing stress. Concentration of cell-wall components in leaves and stems declined with increasing stress (leaves: 214 to 198; stems 652 to 587 g/kg dry matter) Concentration of crude protein (CP) and in vitro digestible dry matter (IVDDM) in stems increased with stress (CP: 109 to 121; IVDDM 496 to 538 g/kg dry matter). Stress occurring during the vegetative stage resulted in forage of higher quality while stress at the flower stage resulted in a 40% leaf loss and forage of lower quality.